2013
DOI: 10.1063/1.4825175
|View full text |Cite
|
Sign up to set email alerts
|

Sequence dependent free energy profiles of localized B- to A-form transition of DNA in water

Abstract: DNA carries an inherent polymorphism, which surfaces under various external conditions. While B-form remains predominant under normal physiological conditions for most of the DNA sequences, low humidity and increased ion concentration cause B- to A-form transition. Certain proteins and molecules also sometimes cause local deformation of the DNA to the specific A-form. Previous experimental and computational studies focused on the overall B- to A-form transition. Here for the first time we investigated thermody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 91 publications
0
38
0
Order By: Relevance
“…We have evidencef rom our earlier study [10] that free energy cost for B!At ransition along Zp' is much less compared to other available choices. Therefore, we recently proposed, [10] followingT sukuba'sc onvention, [21] its dynamicalv ersion Z 0 p .W ea lso showed that Z 0 p and Z p correlate well over severalc rystal structures. There are several parameters that define A-and B-form of DNA.…”
Section: Choice Of the Reaction Coordinatementioning
confidence: 84%
See 4 more Smart Citations
“…We have evidencef rom our earlier study [10] that free energy cost for B!At ransition along Zp' is much less compared to other available choices. Therefore, we recently proposed, [10] followingT sukuba'sc onvention, [21] its dynamicalv ersion Z 0 p .W ea lso showed that Z 0 p and Z p correlate well over severalc rystal structures. There are several parameters that define A-and B-form of DNA.…”
Section: Choice Of the Reaction Coordinatementioning
confidence: 84%
“…Based on the general Dickerson-Drew dodecamer [23] sequence d(CGCGAATTCGCG) 2 ,w eh ave designed twelve DNA sequences of 13 base pairs each, which can be described in general by d(CGCGXXYYYCGCG) 2 ,w here X/Y can be either A, T, C, or G. Reason for keeping the CG sequences in both termini is to reducet he chances of fraying at the ends. Note that in our previouss tudy, [10] all ten dinucleotide steps were flankedb y different steps. The p is the projection ofp on the unit vectorẑ.T he valueso fZ p and Z 0 p for the canonical A-and B-forms are shown.…”
Section: The Design Of Dna Sequencesmentioning
confidence: 86%
See 3 more Smart Citations